Clinicopathological features and prognostic significance of site-specific metastasis in gastric cancer: a population-based, propensity score-matched analysis - Xingbiao Huang; Zhe Li; Qiuyan Weng (Discover Oncology)
Abstract Objective Distant metastasis complicates gastric cancer management and worsens patient outcomes. Understanding the clinicopathological characteristics and prognostic impact of site-specific metastases is crucial for improving treatment strategies and survival prediction. Methods Data from 8338 metastatic gastric cancer patients (2010–2015) were retrieved from the SEER database. Patients were categorized by metastatic organ involvement. Chi-square tests analyzed clinicopathological differences. Cancer-specific survival (CSS) was assessed using Kaplan–Meier curves and the log-rank test. Independent prognostic factors were identified through Cox regression analysis. Propensity score matching minimized group heterogeneity. Results The liver was the most common metastatic site (43.20%). Patients with bone, brain, or lung metastases had significantly shorter CSS compared to those without these metastases. CSS differences between liver metastasis and non-metastasis were not significant. Propensity score matching confirmed shorter CSS in patients with bone and lung metastases. Single-site metastasis had a better prognosis than multiple-site metastasis, with liver-only metastasis showing the best survival and bone-only metastasis the worst. Multivariate Cox regression identified bone, brain, and lung metastases, age, histology, tumor grade, T stage, N stage, primary tumor resection, and chemotherapy as independent prognostic factors. Conclusions The metastatic site significantly influences the prognosis of gastric cancer. Single-site metastasis offers a survival advantage over multiple-site involvement, with liver metastasis showing a better prognosis and bone metastasis the worst. These findings emphasize the importance of site-specific management and the prognostic value of metastatic patterns in gastric cancer.